POLITOMOUS VS. DICHOTOMOUS ITEMS: A METHODOLOGICAL STUDY - López Pina, José Antonio (Anales de Psicología / Annals of Psychology, 2008)
In this report we compare five response formats for politomous items, from the original format (four categories) to dichotomous format. Different psychometric analysis (item analysis, study of the reliability, principal component analysis and ability analysis) have been done on the five different formats. These psychometric analyses show that two categories can obtain as information as four. Then it is necessary to study the appropriate categories in the items before to apply the test.